Analysis of Risk Factors for Cognitive Frailty: A Meta-Analysis - Hendriani, Nani; Roza Mulyana (HM Publisher, 2024)
Background: Cognitive frailty (CF) is a syndrome characterized by cognitive and physical decline in older adults, which increases the risk of disability, dependency, and mortality. This study aims to identify and analyze risk factors for CF incidence through a systematic review and meta-analysis. Methods: A literature search was conducted on PubMed, Scopus, and Web of Science databases until June 2024. Observational studies reporting associations between potential risk factors and CF incidence in the elderly population were included. Two independent researchers performed study selection, data extraction, and risk of bias assessment. Meta-analysis was performed using a random effects model, and heterogeneity between studies was evaluated. Results: A total of 25 studies (n=45,678 participants) met inclusion criteria. Meta-analysis showed that advanced age (OR=1.89; 95% CI 1.65-2.16), female gender (OR=1.38; 95% CI 1.19-1.60), history of cardiovascular disease (OR=1.52; 95% CI 1.23-1.87), diabetes mellitus (OR=1.45; 95% CI 1.18-1.78), depression (OR=2.08; 95% CI 1.72-2.51), and low physical activity (OR=1.63; 95% CI 1.35-1.97) are risk factors significant for the incidence of CF. Low educational level (OR=1.71; 95% CI 1.43-2.04), low socioeconomic status (OR=1.58; 95% CI 1.29-1.93), and smoking history (OR=1.31; 95% CI 1.05-1.64) were also associated. with an increased risk of CF. Conclusion: This study identified several modifiable and nonmodifiable risk factors for CF occurrence. Interventions targeting these risk factors may help prevent or delay the development of CF in older adults.